PENERAPAN TEORI BELAJAR KOGNITIF: STUDI KASUS DALAM PENINGKATAN HASIL BELAJAR MATERI METAMORFOSIS KELAS 3 SDN 018 LONG KALI - Nurvita Sugiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this research is to determine the cognitive learning outcomes in the teaching of metamorphosis in Grade III at SDN 018 Long Kali. The research method used is qualitative research, with respondents including teachers, students, and the school principal. Respondents were selected using purposive sampling based on the research objectives. Snowball sampling was applied through the involvement of participants as aligned with the respondents.The research procedure began with the researcher developing instruments and learning tools based on cognitive learning theory to improve student learning outcomes. The research was carried out through interview and observation techniques. Data analysis involved preliminary and final conclusions derived throughout the interview process.The research results showed that the teacher respondent had prepared, implemented, and evaluated the application of cognitive learning theory-based teaching to improve student learning outcomes on the metamorphosis topic in Grade III at SDN 018 Long Kali. The student respondents had also prepared, participated in the learning activities, and achieved cognitive learning outcomes. Meanwhile, the principal respondent had facilitated the preparation, implementation, and evaluation of the cognitive theory-based learning, resulting in improved student learning outcomes